Isolated Post-Shunt Metopic Synostosis and Neural Tube Defects. Issue 5 (July 2018) - Abouhassan, William; Chao, John An Kuang; Murthy, Ananth S.
Abstract : Background: Craniosynostosis is an uncommon complication after shunting procedures for congenital hydrocephalus. We report a case of a child with myelomeningocele and normocephaly at the time of birth. She underwent ventricular shunting for Chiari malformation and hydrocephalus at 3 days of age. An immediate postoperative CT scan confirmed all sutures were open. Serial CT scans document an open metopic suture at 2 months, closed metopic suture at 5 months, and trigonocephaly at 11 months with concomitant slit ventricle syndrome, and collapsed lateral and third ventricles. Methods: An Ovid MEDLINE search within the dates of 1948 through 2017, using the keywords "synostosis AND shunt" was carried out. A tabulation of all patients and their respective synostosis patterns were recorded. Results: We identified 8 case series and 2 case reports during 43 years (1966–2017). Seventy-eight patients with 79 suture synostosis patterns were identified (one patient underwent a second cranial reconstruction for identification of a separate, newly formed synostosis). Eighteen (30.5%) cases were associated with a neural tube defect (NTD). Patients with NTD and secondary craniosynostosis had on average earlier age of shunt placement ( P  = 0.001), craniosynostosis presentation ( P  = 0.146), and cranioplasty ( P  = 0.325) than secondary craniosynostosis patients without NTD. Conclusions: Ventricular shunt drainage in treating hydrocephalus rarely may lead to early synostosis and cranial deformity, especially in patients with NTDs. Early shunt placement poses significant risk in patients with NTD. Close follow-up may be necessary to evaluate overdrainage and cranial deformity after shunting procedures.